2020
DOI: 10.1093/cercor/bhaa159
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline Release from Locus Coeruleus Terminals in the Hippocampus Enhances Excitation-Spike Coupling in CA1 Pyramidal Neurons Via β-Adrenoceptors

Abstract: Abstract Release of the neuromodulator noradrenaline signals salience during wakefulness, flagging novel or important experiences to reconfigure information processing and memory representations in the hippocampus. Noradrenaline is therefore expected to enhance hippocampal responses to synaptic input; however, noradrenergic agonists have been found to have mixed and sometimes contradictory effects on Schaffer collateral synapses and the resulting CA1 output. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 78 publications
(132 reference statements)
1
25
0
Order By: Relevance
“…Although norepinephrine can bind to both α-or β-adrenergic receptors, synaptic information and plasticity in the hippocampus would depend largely on the activation of β-adrenergic receptors (A. Kemp & Manahan-Vaughan, 2008 (Bacon et al, 2020) and improves memory through a βadrenergic-dependent mechanism (Hagena et al, 2016;N. Hansen & Manahan-Vaughan, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although norepinephrine can bind to both α-or β-adrenergic receptors, synaptic information and plasticity in the hippocampus would depend largely on the activation of β-adrenergic receptors (A. Kemp & Manahan-Vaughan, 2008 (Bacon et al, 2020) and improves memory through a βadrenergic-dependent mechanism (Hagena et al, 2016;N. Hansen & Manahan-Vaughan, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although norepinephrine can bind to both α-and β-adrenergic receptors, synaptic information and plasticity in the hippocampus is proposed to depend largely on the activation of βadrenergic receptors (Kemp & Manahan-Vaughan, 2008). Indeed, LC stimulation modulates hippocampal synaptic strength (Hansen & Manahan-Vaughan, 2015;Kemp & Manahan-Vaughan, 2012, spike coupling of CA1 pyramidal neurons (Bacon et al, 2020) and improves memory through a β-adrenergic-dependent mechanism (Hagena et al, 2016;Hansen & Manahan-Vaughan, 2015). In agreement, we observed that the intrahippocampal blockade of β-adrenergic receptors with propranolol prevented the increase of novel object-recognition memory persistence produced by AM6545.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the effect of noradrenaline on both pathways we used bath application of 20 μM noradrenaline (NA) that we have found to be a maximal effective dose for cellular and synaptic properties within hippocampal slices [ 31 ]. Application of 20 μM noradrenaline had no effect on EPSC amplitudes ( Fig 1E ; 126.1 ± 13.9% and 107.1 ± 12.1% of baseline measured at 1 st and 4th pulses, n = 14, p = 0.44) or facilitation ratios ( Fig 1E ; p = 0.08; Measured at 1 st to 4 th pulse).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, salience experiences also upregulate noradrenaline activity (Izquierdo and Medina 1997;Roozendaal and McGaugh 2011). Further, adrenoreceptors activation in the hippocampus increases CA1 neurons excitability (Bacon, Pickering, and Mellor 2020), promotes synaptic plasticity and memory encoding (Lemon et al 2009;Sara 2009), and is required for novelty-induced changes in hippocampal spatial code (Tanila 2001). Finally, inhibition of the locus coeruleus projections to the hippocampus, known to release both dopamine and noradrenaline (Kempadoo et al 2016; Ranjbar-Slamloo and Fazlali 2020), impairs the accumulation of fields near newly rewarded locations (Kaufman, Geiller, and Losonczy 2020).…”
Section: Discussionmentioning
confidence: 99%